2019
DOI: 10.1261/rna.069534.118
|View full text |Cite
|
Sign up to set email alerts
|

Human PRPF40B regulates hundreds of alternative splicing targets and represses a hypoxia expression signature

Abstract: Altered splicing contributes to the pathogenesis of human blood disorders including myelodysplastic syndromes (MDS) and leukemias. Here we characterize the transcriptomic regulation of PRPF40B, which is a splicing factor mutated in a small fraction of MDS patients. We generated a full PRPF40B knockout (KO) in the K562 cell line by CRISPR/Cas9 technology and rescued its levels by transient overexpression of wild-type (WT), P383L or P540S MDS alleles. Using RNA sequencing, we identified hundreds of differentiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 87 publications
(109 reference statements)
0
25
0
Order By: Relevance
“…We observed that there was an enrichment of genes related to RNA splicing and metabolism among the intron-retaining genes. Splicing factors affected by IR particularly in Ctcf +/- liver and kidney such as Srsf1, Esrp2 and Prpf40b have been previously reported to be associated with the regulation of AS including IR [ 35 , 59 , 60 ]. In addition to splicing, genes involved in metabolic processes were affected by IR in Ctcf haploinsufficient liver.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that there was an enrichment of genes related to RNA splicing and metabolism among the intron-retaining genes. Splicing factors affected by IR particularly in Ctcf +/- liver and kidney such as Srsf1, Esrp2 and Prpf40b have been previously reported to be associated with the regulation of AS including IR [ 35 , 59 , 60 ]. In addition to splicing, genes involved in metabolic processes were affected by IR in Ctcf haploinsufficient liver.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that there was an enrichment of genes related to RNA splicing and metabolism among the intron-retaining genes. Splicing factors affected by IR particularly in Ctcf +/liver and kidney such as Srsf1, Esrp2 and Prpf40b have been previously reported to be associated with the regulation of AS including IR [35,57,58]. In addition to splicing, genes involved in metabolic processes were affected by IR in Ctcf haploinsufficient liver.…”
Section: Discussionmentioning
confidence: 99%
“…Alternative splicing differences were analysed by an in-house pipeline using replicate MATS (rMATS 4.0.2) and filtered based on cut-offs of FDR ≤ 0.05, an absolute change in percent spliced in (|ΔPSI|) ≥ 0.1 ( 35 , 36 ). In addition, events with a mean junction count <20 for either condition, as well as those with <10 inclusion or spliced junction counts for both conditions, were filtered out to enhance the reliability of our splicing dataset.…”
Section: Methodsmentioning
confidence: 99%